Pengembangan Perilaku Sosial Emosional Anak Usia Dini Melalui Kegiatan Bermain Peran di Masa Pandemi - Nurul Ismaiyah (Institut Agama Islam Negeri Madura, 2022)
Emotional social behavior early childhood is very important to be developed even during a pandemic. Role playing is an alternative to develop children's social and emotional well being by providing positive values in every story that is conveyed and played by children. This is done because early childhood gains knowledge through play activities that are carried out and become experiences in themselves. The purpose of this research is to provide solutions and steps that can be taken to develop children's social emotional behavior through role playing during the pandemic. The research method used is naturalistic qualitative. The results of the study show that with the application of role playing, children become more receptive to knowledge about Covid-19 pandemic and maintain good social interactions while maintaining health protocols.